DIAGNOSTIC VALUE OF NEUTROPHIL-LYMPHOCYTE RATIO TO DIFFERENTIATE ISCHEMIC AND HEMORRHAGIC STROKE - Martina Rentauli; Liong Boy Kurniawan; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
IntroductionStroke is a neurologic emergency disease and the main cause of high mortality. Inflammatory process in stroke due to cell and tissue damage causes increase of leucocyte prominently neutrophil. Neutrophil Limphocyte Ratio is an easy-to-measure inflammatory marker. There is only few data of RNL in Indonesia.MethodsThis was a retrospective cross-sectional study using secondary data from Medical Record RSUP Wahidin Sudirohusodo, Makassar. Leucocyte, neutrophil and lymphocyte first data were taken from adult stroke diagnosed patients. Data statistically analyzed and diagnostic value of NLR was determined by ROC curve analysis.Results dan DiscussionTotal of 402 patients were enrolled, 214 (54.72%) with ischemic stroke and 182 (46.8) with hemorrhagic stroke. There was a significant RNL difference between ischemic stroke (median 7.23) and hemorrhage stroke (median 3.65) (p<0.001). Using cut off 5.18, ROC curve showed of AUC 0.730 which had weak perfomance to differentiate ischemic and hemorrhagic stroke with sensitivity 67.8% and specificity 68.6%.Conclusion and SuggestionNLR in hemorrhagic stroke is higher than ischemic stroke. We suggest further studies with larger and more evenly distributed samples and consideration of sampling time.